2016
DOI: 10.1590/s1980-6574201600030004
|View full text |Cite
|
Sign up to set email alerts
|

Value of pre-cue information for motor tasks performed by children with developmental coordination disorder (DCD)

Abstract: People commonly use pre-cue information to advance and reduce the information processing time required for a motor task (e.g., motor planning). However, children with developmental coordination disorder (DCD) exhibit difficulties performing pre-cued goal-directed tasks. The purpose of the present study was to investigate the use of valid, neutral, and invalid pre-cue information for a goal-directed task. The participants were 11 children with DCD (mean age = 7.94 yrs.) and 11 typically developed (TD) age-and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…Gonzalez et al's ( 2016 ) investigation of target-directed hand-eye coordination showed larger effects under cued conditions for eye ( d = 1.66, 95% CI = [0.78, 2.54]) and hand movement ( d = 1.22, 95% CI = [0.35, 2.09]) compared with uncued conditions ( d = 0.70, 95% CI = [−0.20, 1.59] and d = 0.62, 95% CI = [−0.27,1.51], respectively). All effects of target-directed pointing were non-significant but primarily of moderate magnitude; these results were all reported from one study (Gama et al, 2016 ). The only significant effect for manual stacking was reported under unimanual, hand movement conditions ( d = 1.40, 95% CI = [0.53, 2.27]), whereas bimanual conditions revealed moderate, but non-significant effects (Warlop et al, 2020a ).…”
Section: Resultssupporting
confidence: 63%
See 3 more Smart Citations
“…Gonzalez et al's ( 2016 ) investigation of target-directed hand-eye coordination showed larger effects under cued conditions for eye ( d = 1.66, 95% CI = [0.78, 2.54]) and hand movement ( d = 1.22, 95% CI = [0.35, 2.09]) compared with uncued conditions ( d = 0.70, 95% CI = [−0.20, 1.59] and d = 0.62, 95% CI = [−0.27,1.51], respectively). All effects of target-directed pointing were non-significant but primarily of moderate magnitude; these results were all reported from one study (Gama et al, 2016 ). The only significant effect for manual stacking was reported under unimanual, hand movement conditions ( d = 1.40, 95% CI = [0.53, 2.27]), whereas bimanual conditions revealed moderate, but non-significant effects (Warlop et al, 2020a ).…”
Section: Resultssupporting
confidence: 63%
“…There was a large overall effect (d = 0.87, 95% .51], respectively). All effects of target-directed pointing were non-significant but primarily of moderate magnitude; these results were all reported from one study (Gama et al, 2016). The only significant effect for manual stacking was reported under unimanual, hand movement conditions (d = 1.40, 95% CI = [0.53, 2.27]), whereas bimanual conditions revealed moderate, but non-significant effects (Warlop et al, 2020a).…”
Section: Reaching and Manual Controlmentioning
confidence: 63%
See 2 more Smart Citations
“…A slow RT can result from various brain diseases, disorders and acquired conditions that affect white matter conduction, gray matter neurotransmission, and efficiency of cognitive neural networks (Klotz, Johnson, Wu, Isaacs, & Gilbert, 2012). Therefore, RT deficits have been well demonstrated in children with attention deficit hyperactivity disorder (ADHD; Sjöwall, Roth, Lindqvist, & Thorell, 2013), developmental coordination disorder (DCD; Gama, Ferracioli, Hiraga, & Pellegrini, 2016; Johnston, Burns, Brauer, & Richardson, 2002), dyslexia (Kaltner & Jansen, 2014), and autism spectrum disorder (ASD; Herrero & Crocetta, 2015). Poor RT has also been associated with childhood obesity and high body mass index (BMI) values (Gentier et al., 2013; Skurvydas et al., 2009).…”
Section: Introductionmentioning
confidence: 99%